2019
DOI: 10.18632/aging.102229
|View full text |Cite
|
Sign up to set email alerts
|

Kindlin-3 in platelets and myeloid cells differentially regulates deep vein thrombosis in mice

Abstract: Platelets and myeloid cells cooperate to promote deep vein thrombosis (DVT). Here we evaluated the role of kindlin-3, a key integrin activator in these cells, in regulating stenosis-induced DVT in mice. DVT was significantly suppressed in mice that express a kindlin-3 mutant defective for integrin binding, showing that kindlin-3-mediated integrin signaling in blood cells is required for DVT. While platelet-specific deficiency of kindlin-3 in Kindlin-3fl/flPF4-Cre mice significantly suppressed DVT, deficiency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…As an essential integrin activator, 18 the presence of kindlin-3 in neutrophils also negatively regulates NET release, which can subsequently suppress venous thrombosis in mice, as demonstrated in our previous studies. 19 , 36 Therefore, we hypothesized that the elevated expression of kindlin-3 in myeloid cells found in MSC-treated COVID-19 patients might help restrict NET release and thereby reduce the risk of venous thrombosis. To test this hypothesis, we generated mice exogenously expressing EGFP-kindlin-3 in bone-marrow hematopoietic cells as well as mice exogenously expressing EGFP alone as the control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an essential integrin activator, 18 the presence of kindlin-3 in neutrophils also negatively regulates NET release, which can subsequently suppress venous thrombosis in mice, as demonstrated in our previous studies. 19 , 36 Therefore, we hypothesized that the elevated expression of kindlin-3 in myeloid cells found in MSC-treated COVID-19 patients might help restrict NET release and thereby reduce the risk of venous thrombosis. To test this hypothesis, we generated mice exogenously expressing EGFP-kindlin-3 in bone-marrow hematopoietic cells as well as mice exogenously expressing EGFP alone as the control.…”
Section: Resultsmentioning
confidence: 99%
“…SARS-CoV-2 can attack the vast majority of cells in the body, causing damage to multiple tissues and organs. 36 , 39 Moreover, COVID-19 patients have characteristic hyperinflammation and immune-function disorders. 40 42 In this regard, MSCs reportedly can have powerful effects on the regulation of immune function and can reduce inflammation and consequent fibrosis in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, PAD4 inhibitors BB-Cl-amidine can relieve NETs-related vascular endothelial injury to some extent [ 173 ]. Recently, a novel finding suggested that PAD4 inhibitor GSK484 can also inhibit NETs-induced thrombosis by affecting kindlin-3 in neutrophils [ 174 ]. Therefore, it is hypothesized that PAD4 inhibitors have a great relevance to the prevention of ED.…”
Section: Diseases and Treatmentmentioning
confidence: 99%
“…Knockout of PAD4 or use of PAD4 inhibitor GSK484 will inhibit heparin-induced thrombocytopenia/thrombosis (HIT) thrombocytopenia and thrombosis ( Perdomo et al., 2019 ). PAD4 inhibitor GSK484 can also affect kindlin-3 in mouse neutrophils and inhibit thrombosis caused by NETs ( Yan et al., 2019 ). The PAD4 inhibitor Cl-amidine affects endothelial function and prethrombotic phenotype by blocking NETs ( Knight et al., 2013 ), and can also inhibit tissue damage associated with inflammatory bowel disease mouse models ( Chumanevich et al., 2011 ).…”
Section: Potential Therapeutic Targetsmentioning
confidence: 99%